Accuracy of EBRA‐cup measurements after reconstruction of severe acetabular defects at revision THR. Issue 7 (20th February 2020) - Abrahams, John M.; Callary, Stuart A.; Jang, Sung W.; Hewitt, Joseph; Howie, Donald W.; Solomon, Lucian B.
Abstract: Radiostereometric analysis (RSA) is the most accurate method of measuring component migration using radiographs but is restricted to use in prospective studies. Ein‐Bild‐Roentgen‐analyze (EBRA)‐Cup can be used retrospectively, but its accuracy to measure component migration following revision is unknown. This study aimed to determine the accuracy of EBRA‐Cup measurements of uncemented acetabular component migration after revision total hip replacement (THR). The secondary aim was to compare the number of cases identified using EBRA‐Cup and RSA as having proximally migrated above and below 1 mm at 2 years postoperatively. EBRA‐Cup measurements were performed on plain antero‐posterior pelvic radiographs taken at the same time as RSA radiographs in a prospective cohort of 53 hips undergoing acetabular revision. At 2 years, the mean difference between the RSA and EBRA‐Cup measurements for 17 components used to treat pelvic discontinuity was 0.90 mm, significantly greater than the mean difference of 0.28 mm for 36 components without discontinuity ( P = .0001). The mean difference between the RSA and EBRA‐Cup measurements at 2 years for hips that were reconstructed with an acetabular component alone, 0.28 mm, was significantly lower than hips that were reconstructed with an acetabular component in combination with an augment and/or cage, 0.74 mm ( P = .0005). In conclusion, EBRA‐Cup can accurately measure migration of uncemented acetabular components used at revision THR. The presence of pelvic discontinuity, and addition of augments and cages, significantly influenced the accuracy of EBRA‐Cup measurements. EBRA‐Cup and RSA had good agreement on classification of components that migrated proximally above or below 1 mm at 2 years, with 100% sensitivity, and 87% specificity.